Detection of Chlamydia trachomatis by ligase chain reaction compared with polymerase chain reaction and cell culture in urogenital specimens. Issue 6 (December 1995) - de Barbeyrac, B; Rodriguez, P; Dutilh, B; Le Roux, P; Bébéar, C
Abstract : OBJECTIVE–The aim of this study was to evaluate the newly developed ligase chain reaction (LCR) assay for the detection of Chlamydia trachomatis in urogenital specimens using cell culture and Amplicor PCR for comparison. SUBJECTS–Two hundred and eighty patients attending hospital or urban STD clinics (high-risk population, 62 men and 84 women) and obstetric/gynaecology clinics (low-risk population, 134 women) in Bordeaux, France. METHODS–Specimens from men were tested with LCR on urethral swabs and urine, with Amplicor or urine, with cell culture on urethral swabs. Specimens from women were tested with LCR, Amplicor and cell culture on endocervical swabs and with LCR on urine. When the three methods generated different results, the LCR and Amplicor tests were repeated on the remaining samples. Samples with discordant LCR and Amplicor results and a negative culture were further analysed by major outer membrane protein gene omp1-PCR. RESULTS–After analysis of discrepant results, the overall prevalence was 7.5% (21/280) calculated on the basis of an expanded "gold standard" defined as culture positive or LCR plus Amplicor positive or omp1-PCR positive for discrepant results between LCR and Amplicor tests. Of the 21, 20 were detected by LCR, 17 by Amplicor and culture. The specificity of LCR and Amplicor was 99.6%. CONCLUSION–The LCR Chlamydia trachomatis test is a highly sensitive nonculture technique and a good alternative test for the detection of chlamydial infections.